Adversity quotient of outstanding students with limited conditions - Hidayati, Isnaya Arina; Taufik, Taufik (Universitas Muhammadiyah Surakarta, 2020)
This study aims to explore and explain the dynamics of the striving force namely, the supporting and inhibiting factors of high achieving students striving force with necessitous condition. The informant characteristics of this study are high achieving students with necessitous condition (students who are needy with the broken home family and experiencing violence from their family) who attend junior and senior high school and college students. There are 3 informants and 9 informants complementary, with interview method. The results of this study are; 1) Informants control economic difficulties with frugal behavior and concerned attitudes. Good self-regulation in controlling difficult situations so as not to widen and influence the educational dimension. Resilience behavior is more appear in informants of victims of broken homes and survivors of domestic violence. Gratitude makes the informant more eager to rise from adversity to achieve a better life, accompanied by strong motivation and relational efficacy between mother and informant. 2) Supporting factor is derived from internal factors such as the competitiveness, coping behavior and the ability of improvement (resilience), visionary and strong internal motivation, self-awareness and the ability to think positively with gratitude. While external factors mostly come from social support of family, other students and community. 3) Inhibiting factors namely are the problem of emotion-regulation such as less stable emotional state, poverty, dysfunction of family’s role and the problem of fatherless families. It is concluded that a compensation made by the informant with self-regulation, gratitude in increasing resilience and the relational efficacy of family members in strengthening the struggle for achievement